Study analysis of the Influence of Internal Factors on Export-Based Entrepreneur in Magelang City - Suwardi - Suwardi; Sugiyanta - Sugiyanta; Paniya - Paniya; Achmad - Zaenuddin; Subandi - Subandi (Politeknik Negeri Semarang, 2022)
The success of a business is influenced by internal and external factors of the company. This study aims to determine the influence of Technical Factors, HR Factors, Operational Factors, and Financial Factors on SME Performance either partially or simultaneously. The data collection method in this study used observation, questionnaires and interviews conducted in Magelang City. The population used in this study is export-based SMEs in Magelang, while the sample used is 30 export-based SMEs. The analysis technique used is multiple regression analysis. The results showed that the influence of Technical Factors, HR Factors, Operational Factors, and Financial Factors had a positive relationship to UKM Performance, but only HR Factor variables had a significant influence on UKM Performance. The coefficient of determination in this study is 36.6 % which means that the influence of the independent variable on the dependent variable studied in this study is only 36.6% and the remaining 63.4% is explained by other variables outside this study